PENGARUH KUALITAS LAYANAN, KUALITAS SISTEM DAN KUALITAS INFORMASI SISTEM INFORMASI APLIKASI SAP TERHADAP KEPUASAN PENGGUNA DAN KINERJA INDIVIDU DI KANTOR PUSAT PT PUPUK KALIMANTAN TIMUR - Anisa Dwi Handini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this quantitative study is to examine factors that influence the satisfaction of Enterprise Resource Planning (ERP) users, particularly users of System Application and Product in Data Processing (SAP), by adapting system information success model developed by DeLone and McLean (2003). This research uses primary data taken from employees of the Head Office of PT Pupuk Kalimatan Timur. The data are analyzed using SmartPLS 2.0. The result this research shows that service quality, system quality, and information quality positively influence the SAP users’ satisfaction. This stdystudy also confirms that their satisfaction gives a positive effect on the ndividual performance of employees. Keywords : service quality, system quality, information quality, satisfaction of SAP user, individual performance